1996
DOI: 10.1021/cm9602959
|View full text |Cite
|
Sign up to set email alerts
|

Negative Thermal Expansion in ZrW2O8 and HfW2O8

Abstract: Isostructural ZrW2O8 and HfW2O8 show strong negative thermal expansion from 0.3 K up to their decomposition temperatures of approximately 1050 K. This behavior is especially unusual because these compounds are apparently cubic over their entire existence range. Detailed structural studies of ZrW2O8 were conducted using high-resolution neutron powder diffraction data taken at 14 temperatures from 0.3 to 693 K. Below 428 K, ZrW2O8 adopts the acentric space group P213 and has a well-ordered structure containing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
394
2
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 538 publications
(437 citation statements)
references
References 60 publications
36
394
2
5
Order By: Relevance
“…The negative slope of the amorphization boundary is understandable because a moderate increase in temperature can increase the kinetics slightly and the onset of pressure-induced structural change (amorphization) can occur at a lower pressure. This has been found experimentally [14,24]; D: decomposed state [20,24]; H: hexagonal phase [20]; C(α): cubic α-phase [11]; C(β): cubic β-phase [18]; O(γ ): orthorhombic γ -phase [23]. The solid lines are the proposed phase boundaries.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…The negative slope of the amorphization boundary is understandable because a moderate increase in temperature can increase the kinetics slightly and the onset of pressure-induced structural change (amorphization) can occur at a lower pressure. This has been found experimentally [14,24]; D: decomposed state [20,24]; H: hexagonal phase [20]; C(α): cubic α-phase [11]; C(β): cubic β-phase [18]; O(γ ): orthorhombic γ -phase [23]. The solid lines are the proposed phase boundaries.…”
Section: Resultssupporting
confidence: 58%
“…It may be mentioned here that an orientational disorder of polyatomic units/ions is known to result in the presence of more Raman lines than expected from group theory [17]. The structure of zirconium tungstate consists of interpenetrating sublattices of zirconium cations and tungstate anions, and its high-temperature phase has been reported to have oxygen disorder leading to two configurations of tungstate ions [18]. Hence the additional peaks may be attributed to the existence of some amount of residual orientational disorder of tungstate ions in the annealed samples.…”
Section: Resultsmentioning
confidence: 79%
“…Quite a few inorganic materials show either volume or uniaxial negative thermal expansion ͑NTE͒ 1 with ZrW 2 O 8 as the most prominent example of large, isotropic NTE over a wide temperature range. [2][3][4] In ␣-ZrW 2 O 8 ͑low temperature phase͒ and ␤-ZrW 2 O 8 ͑high temperature phase͒, the linear expansion coefficient ␣ is −8.7ϫ 10 −6 and −4.9ϫ 10 −6 K −1 , respectively. 5 In contrast, only very few examples of ͑uniaxial͒ NTE in organic systems are known so far ͑see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in materials that exhibit negative thermal expansion (NTE) was renewed after the report [1] of high and isotropic NTE in Zr(WO 4 ) 2 over a wide temperature range, leading to extensive work and several reviews on the subject [2][3][4][5]. The structure of Zr(WO 4 ) 2 and several other NTE materials consist of corner sharing tetrahedral and octahedral units.…”
mentioning
confidence: 99%
“…From Raman spectroscopic investigations on Zr(WO 4 ) 2 as a function of pressure and temperature, the phonons responsible for NTE have been identified, and it has been shown that in addition to the librational (rigid-unit) mode at 5 meV, several other phonons of much higher energy also contribute significantly to the NTE in this material [6][7][8][9]. Based on structural analysis transverse displacements of the shared oxygen atoms and consequent rotation of polyhedra [1] was suggested as the cause of NTE in Zr(WO 4 ) 2 . In the context of corner linked structures, Zn(CN) 2 is remarkable, as it has C≡N as the linking species between tetrahedral units instead of a single atom and exhibits twice as much coefficient of NTE (-17x10 -6 K -1 ) [10] as that of Zr(WO 4 ) 2 .…”
mentioning
confidence: 99%